Mode-locking in quadratically nonlinear waveguide arrays - (:unkn) unknown (My University, 2022)
A two-dimensional theoretical model is constructed to describe optical mode-locking (ML) in quadratically nonlinear waveguide arrays (QWGAs). Steady-state solutions of the considered model are obtained by a modified pseudo-spectral renormalization algorithm, and the mode-locking dynamics of the model are investigated through direct simulation of the nonlinear evolution and a linear stability analysis of the solutions. It is shown that stable mode-locking of elliptic steady-state solutions in quadratically nonlinear waveguide arrays are possible for a wide range of parameters, suggesting that quadratically nonlinear materials are well suited for producing stable mode-locked states for a wide range of applications. (C) 2022 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement
Keywords: Fizik; Elektromanyetizma, Akustik, Isı Transferi, Klasik Mekanik ve Akışkanlar Dinamiği; Optik; Temel Bilimler; Physics; Electromagnetism, Acoustics, Heat Transfer, Classical Mechanics and Fluid Dynamics; Optics; Natural Sciences; OPTİK; Temel Bilimler (SCI); OPTICS; PHYSICS; Natural Sciences (SCI)